Transformation of Gunkanjima (Battleship Island): from a coalmine island to a modern industrial heritage tourism site in Japan. Issue 2 (15th March 2017) - Hashimoto, Atsuko; Telfer, David J.
ABSTRACT: Gunkanjima Island (Battleship Island) is an abandoned coalmine and community off the coast of Nagasaki, Japan. At its peak, the island was fuelling the industrialisation of modern Japan, home to a community of over 5000 residents with one of the highest population densities in the world and the site of early modern concrete high-rise buildings. With the shift to oil, the island soon became abandoned going into decay. A recent rise in media attention and the inclusion as a 2015 UNESCO World Heritage Site has generated interest in industrial heritage tourism on the island. This paper explores the rise and fall of the island as a coalmine and the transition to an industrial heritage tourism site. A framework is presented illustrating the transformation of industrial sites into industrial heritage tourist attractions.